2005
DOI: 10.1523/jneurosci.5080-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Mitigates Cognitive Deficits in a Mouse Model of Alzheimer's Disease

Abstract: Epidemiological studies suggest that individuals with greater education or more cognitively demanding occupations have diminished risk of developing dementia. We wanted to test whether this effect could be recapitulated in rodents using environmental enrichment, a paradigm well documented to attenuate behavioral deficits induced by various pathological insults. Here, we demonstrate that learning and memory deficits observed in a transgenic mouse model of Alzheimer's disease can be ameliorated by enrichment. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
301
6
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(337 citation statements)
references
References 89 publications
(103 reference statements)
20
301
6
10
Order By: Relevance
“…AD pathogenesis was recently found to be modulated by environmental factors such as education, mental/leisure activity, depression, and stress, some of which affect signaling events in the brain [64][65][66]. Remarkably, we found in our recent study that β2-adrenoceptor signaling, which mediates the stress response in animals, regulates γ-secretase activity and senile plaque formation in vivo [67].…”
Section: Discussionmentioning
confidence: 55%
“…AD pathogenesis was recently found to be modulated by environmental factors such as education, mental/leisure activity, depression, and stress, some of which affect signaling events in the brain [64][65][66]. Remarkably, we found in our recent study that β2-adrenoceptor signaling, which mediates the stress response in animals, regulates γ-secretase activity and senile plaque formation in vivo [67].…”
Section: Discussionmentioning
confidence: 55%
“…Enriched mice transgenic for human APOE3 showed improved learning and memory associated with higher hippocampal levels of presynaptic protein synaptophysin and of NGF, whereas mice transgenic for human APOE4 were unaffected by EE. EE has repeatedly been reported to enhance performance in various cognitive tasks in transgenic mice carrying a double mutation at the level of both APP and PS1 genes, 182,183 in mice carrying the so-called Swedish mutation (SweAPP), [184][185][186] and in AD11 transgenic mice expressing a recombinant anti-NGF factor antibody. 187 The effect of EE on Ab levels and plaque deposition, as well as their impact on cognitive improvement, is controversial.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 97%
“…Among these, APP/PS1 double transgenic mice are an extensively used model, showing progressive age-related development of Aβ accumulation and cognitive deficits (Jankowsky et al 2001;Trinchese et al 2004;van Groen et al 2006;Meyer-Luehmann et al 2009;Filali et al 2011;Janus et al 2015). Furthermore, previous studies have revealed positive results, such as demonstrating various antioxidants (Garcia-Alloza et al 2010;Varamini et al 2014;Yanagisawa et al 2015), neuroprotective agents (Kilgore et al 2010;Peng et al 2012;Li et al 2014), anti-neuroinflammation (Cherry et al 2015;Guo et al 2015), immune therapy (Sudduth et al 2013;Carrera et al 2013;Zhang et al 2015), and nonpharmacological interventions (Liu et al 2011;Jankowsky et al 2005), which can attenuate or even reserve AD-like pathology in APP/PS1 mice. Unfortunately, none of these potentially useful results have been able to be reproduced in clinical therapies for AD patients.…”
Section: Introductionmentioning
confidence: 99%